Climate change negotiations : a guide to resolving disputes and facilitating multilateral cooperation - Sjostedt, Gunnar; Penetrante, Ariel (London : Routledge, Taylor & Francis Group, 2013)
'As the Kyoto Protocol limps along without the participation of the US and Australia, on-going climate negotiations are plagued by competing national and business interests that are creating stumbling blocks to success. Climate Change Negotiations: A Guide to Resolving Disputes and Facilitating Multilateral Cooperation asks how these persistent obstacles can be down-scaled, approaching them from five professional perspectives: a top policy-maker, a senior negotiator, a leading scientist, an international lawyer, and a sociologist who is observing the process. The authors identify the major problems, including great power strategies (the EU, the US and Russia), leadership, the role of NGOs, capacity and knowledge-building, airline industry emissions, insurance and risk transfer instruments, problems of cost benefit analysis, the IPCC in the post-Kyoto situation, and verification and institutional design. A new key concept is introduced: strategic facilitation.'Strategic facilitation' has a long time frame, a forward-looking orientation and aims to support the overall negotiation process rather than individual actors. This book is aimed at academics, university students and practitioners who are directly or indirectly engaged in the international climate negotiation as policy makers, diplomats or experts'--
'Climate negotiations are continually plagued by competing national and business interests that create stumbling blocks to success. This book approaches these blocks from five professional perspectives. They identify major problems, including great power strategies, leadership, the role of NGOs, capacity-and knowledge-building, airline emissions, risk transfer instruments, cost benefit analysis, the IPCC, and verification and institutional design'--
Strategic facilitation of climate change negotiations : an introduction / Gunnar Sjostedt and Ariel Macaspac Penetrante -- The perspective of a Politician : How Decisions are Made / Josef Proell, Helmut Hojesky and Werner Wutscher -- The New Diplomacy from the Perspective of a Diplomat : Facilitation of the Post-Kyoto Climate Talks / Bo Kjellen -- Costs and Uncertainties in Climate Change Negotiations : A Scientist's Perspective / Bert Bolin -- The Observing International Lawyer / Franz Cede and Gerhard Loibl -- The Observing Sociologist / Guy Olivier Faure -- Defining a Politically Feasible Path for Future Climate Negotiations : lessons from the EU-USA divide over the Kyoto Protocol / Urs Steiner Brandt -- Between Two Giants : Lessons from the Russian Policy on the Kyoto Protocol / Vasily Sokolov -- Leadership and Climate Talks : Historical Lessons in Agenda Setting / Steinar Andresen -- NGO Participation in the Global Climate Change Decision-making Process : A Key for Facilitating Climate Talks / Norichika Kanie -- Institutional Capacity to Facilitate Climate Change Negotiations : a need for new thinking / Angela Churie Kallhauge & Lisa van Well -- Stumbling Blocks in a Sectoral Approach : Addressing Global Warming through the Airline Industry / Lucas Bobes -- Overcoming stumbling blocks : Can the Intergovernmental Panel on Climate Change (IPCC) deliver on Adaptation? / Tora Skodvin -- Common but Differentiated Responsibilities : The North-South Divide in the Climate Change Negotiations / Ariel Macaspac Penetrante -- Developing a Legal Toolkit : Institutional Options to Remove Stumbling Blocks in the Climate Change Negotiations / Dirk Hanschel -- Verification as a Precondition for Binding Commitments : Facilitation through Trust / Larry MacFaul -- Difficulties of Benefit-Cost Analysis in Climate Negotiations : Stumbling Blocks for Reaching an Agreement / Charles Pearson -- Proposal for Insurance for Facilitation of Adaptation / Joanne Linnerooth-Bayer, M.J. Mace & Reinhard Mechler -- Strategic Facilitation of Climate Talks / Gunnar Sjostedt and Ariel Macaspac Penetrante.
Includes bibliographical references and index.
Keywords: Climate change mitigation -- International cooperation; Climatic changes -- Government policy -- International cooperation